Improving Linkages and Referrals to the Broader Health System : For Equitable Care Amidst Rapid Growth and Urbanization - World Bank Group (World Bank, Washington, DC, 2019)
In the fragmented care systems of rapidly growing cities, patients can get lost in the shuffle. A cornucopia of providers is spread across the public, private, and nonprofit sectors, making it difficult to track patients and ensure referral completion. Health systems may also lack human and infrastructure resources to meet demand for higher levels of care; where resources are constrained, the few available specialists and underdeveloped emergency medical services may mostly cater to the wealthy, fuelling health inequities. At the same time, perceptions of low-quality in primary care services can lead patients to go directly to hospitals for minor maladies or injuries. Functional referral systems in urban areas of low- and middle-income countries (LMICs) will need to ensure prompt and appropriate transfer to higher-level care, supplemented by primary care strengthening to prevent costly and inefficient self-referrals.